The Perception of Dependence, Investment Decisions, and Stock Prices - UNGEHEUER, MICHAEL; WEBER, MARTIN (Journal of Finance, 2021)
ABSTRACT How do investors perceive dependence between stock returns; and how does their perception of dependence affect investments and stock prices? We show experimentally that investors understand differences in dependence, but not in terms of correlation. Participants invest as if applying a simple counting heuristic for the frequency of comovement. They diversify more when the frequency of comovement is lower even if correlation is higher due to dependence in the tails. Building on our experimental findings, we empirically analyze U.S. stock returns. We identify a robust return premium for stocks with high frequencies of comovement with the market return.